2004
DOI: 10.1002/hlca.200490031
|View full text |Cite
|
Sign up to set email alerts
|

New Acylated Presenegenin Saponins from Two Species of Muraltia

Abstract: Six new acylated bisdesmosidic triterpene glycosides 1 ± 6 were isolated from the roots of Muraltia heisteria (L.) DC., as three inseparable mixtures 1/2, 3/4, and 5/6 of the (E)-and (Z)-3,4,5-trimethoxycinnamoyl derivatives. The compound pair 1/2 along with four known saponins were also isolated from the roots of Muraltia satureioides DC. Their structures were elucidated mainly by spectroscopic experiments including 2D-NMR techniques as 3 (5) and its (Z)-isomer 6, respectively.Introduction. ± In a continuing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
4
9
0
Order By: Relevance
“…The 3-O-position can be substituted by either an acetyl group or an apiose unit, whereas the 4-O-position was acylated by either an (E)-and (Z)-4-methoxycinnamoyl, or (E)-and (Z)-3,4-dimethoxycinnamoyl group, or by an acetyl group. These results corroborated those previously described for saponins isolated from other Polygalaceae belonging to genera Polygala [1] [5] [6] [9] [10] [14 -18], Carpolobia [3], Muraltia [2] [7], and Securidaca [19], and suggested that this sequence may represent a chemotaxonomic marker for the Polygalaceae family. Plant Material.…”
supporting
confidence: 93%
“…The 3-O-position can be substituted by either an acetyl group or an apiose unit, whereas the 4-O-position was acylated by either an (E)-and (Z)-4-methoxycinnamoyl, or (E)-and (Z)-3,4-dimethoxycinnamoyl group, or by an acetyl group. These results corroborated those previously described for saponins isolated from other Polygalaceae belonging to genera Polygala [1] [5] [6] [9] [10] [14 -18], Carpolobia [3], Muraltia [2] [7], and Securidaca [19], and suggested that this sequence may represent a chemotaxonomic marker for the Polygalaceae family. Plant Material.…”
supporting
confidence: 93%
“…From careful analysis with 1D and 2D NMR data (COSY, TOCSY, HSQC and HMBC), the aglycon part of 1 was revealed to be a triterpene of 3, 23-dihydroxyolean-18-en-28-oic acid, characteristic of six methyl singlets at δ 0.68, 0.81, 0.93, 0.97, 0.99, and 1.01, two diastereotopic protons at δ 3.33 and 3.51 ascribable to a CH 2 OH group and a broad singlet at δ 5.14. The position of the double bond at ∆ 18 (19) was evident from the HMBC correlations of two methyl protons at δ 0.97 and 0.99 with the olefinic carbon at δ 134.0 (C-19) and of the proton at δ 5.14 with two carbons at δ 42.3 (C-13) and 49.9 (C-17). The linkage of the CH2OH and the carbonyl carbon groups to two quaternary carbons at C-4 and C-17, respectively, was also secured by the HMBC correlations between two methylene protons at δ 3.33 and 3.51 and the carbon at δ 44.1 (C-4) and between the proton at δ 2.02 (H-16) and the carbonyl carbon at δ 177.0 (C-28).…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] These observations prompted us to continue in our research aimed at finding biologically active and/or novel saponins from plant origin. [18][19][20][21][22][23] Recently, we investigated the suppression effect of the production of cytokine interleukin (IL)-6 in human mast cell (HMC-1) on the methanolic extract of the seeds of N. sativa, which may contribute to the treatment of asthmatic inflammation. Through bioactivity and 1 H NMR monitoring guided fractionation of the methanolic extract of the seeds of N. sativa, six triterpene glycosides were isolated composed of two new compounds, sativosides A (1) and B (2) and four known ones.…”
Section: Introductionmentioning
confidence: 99%
“…From M. heisteria, five pairs of presenegenin glycosides 20/21-28/29 have been isolated. Three of them are new and are also found in M. satureioides (Elbandy et al, 2002b(Elbandy et al, , 2004. All compounds contain one b-D-glucopyranosyl unit at C-3 and one glycosidic chain at C-28 of three to six sugars, eventually acylated.…”
Section: Introductionmentioning
confidence: 96%
“…Most of the saponins characterized in Muraltia (Elbandy et al, 2002b(Elbandy et al, , 2004, Polygala (Sakuma andShoji, 1981a, 1981b;Miyase et al, 1995;Yoshikawa et al, 1995a, b;Zhang et al, 1996aZhang et al, , 1996bZhang et al, , 1998Desbe`ne et al, 1999;Haddad et al, 2003;Mitaine-Offer et al, 2003), Carpolobia by either E/Z-4-methoxy-, or E/Z-3,4-dimethoxy-, or E/Z-3,4,5-trimethoxycinnamoyl groups, or by one acetyl group.…”
Section: Introductionmentioning
confidence: 98%